No Yangtze River Prior to the Late Miocene: Evidence From Detrital Muscovite and K‐Feldspar 40Ar/39Ar Geochronology. Issue 5 (5th March 2021) - Sun, Xilin; Tian, Yuntao; Kuiper, K.F.; Li, Chang'an; Zhang, Zengjie; Wijbrans, J.R.
Abstract: The Yangtze River is the largest river in Asia and its age and evolution has been the subject of debate for more than one century. Here, we applied a combination of detrital muscovite and K‐feldspar 40 Ar/ 39 Ar dating on a set of samples from late Cenozoic Nanjing fluvial gravel sediments (overlain by basalt with ages of ∼22.9 and ∼10.3 Ma) distributed along the lower Yangtze River to trace the late Cenozoic Yangtze drainage. It is found that the characteristic Cenozoic muscovite and K‐feldspar age signals of the upper Yangtze are absent in the gravel sediments, indicating that the upper Yangtze did not supply sediment to the lower Yangtze before at least late Miocene time. These results do not support a prelate Miocene birth of the Yangtze River, but favor an alternative model highlighting later integration of the upper Yangtze into the mid‐lower reaches to form the current Yangtze drainage system. Key Points: New detrital muscovite and K‐feldspar results indicate early Miocene Nanjing gravels sourced from mid‐lower Yangtze The upper Yangtze did not supply sediments to the lower reaches before late Miocene time The Yangtze River developed during late Miocene and Pliocene time